Point-of-Care Ultrasound Training for Family Medicine Residents: Examining the outcomes and feasibility of a pilot ultrasound curriculum - Gordon Yao; Taeyoung Peter Hong; Philip Lee; Joseph Newbigging; Brent Wolfrom (CINQUILL Medical Publishers Inc., 2019)
It is estimated that 50% of deaths due to abdominal aortic aneurysms (AAA) could be prevented by a national screening program [1, 2, 3]. Thanks to technological advancements and cost reductions, point-of-care ultrasound (POCUS) in family medicine (FM) is becoming more prevalent [4, 5]. Despite the potential utility of POCUS in FM, of 224 FM residency programs surveyed, only 21% had developed a curriculum [6]. The main barriers identified to establishing a FM POCUS curriculum in Canadian FM residency programs were lack of trained faculty, lack of adequate equipment and lack of time in the curriculum [6].